CHARACTER BUILDING OF STUDENTS BY GUIDANCE AND COUNSELING TEACHERS THROUGH GUIDANCE AND COUNSELING SERVICES - Nurhasanah Nurhasanah; Qathrin Nida (Jurnal Ilmiah Peuradeun, 2016)
This study aims to determine the process and counseling services performed by guidance and counseling (BK) teachers in coaching the students’ character, with the method descriptive qualitative approach. Guidance and counseling are services of assistance given to students to develop their potential, alleviate the problems, and shape the character of the students in accordance with the norms that exist in the neighborhood. The character building of students can be done through guidance and counseling services that are prevention, alleviation and development. The results showed that the process of guidance and counseling was done not in accordance with established procedures and the implementation of observation and data identification to understand the needs within the framework of the preparation of BK program. Besides, the prevention activities were carried out by providing knowledge about the character of the students through information services, content mastery and group counseling as well as involving students in religious activities at school.